Towards a Theory of Trade Finance - Tim Schmidt-Eisenlohr (Verein für Socialpolitik, 2010)
Cross border transactions are conducted using different payment contracts, the usage of which varies across countries and over time. In this paper I build a model that can explain this observation and study implications from this for international trade. In the model exporters optimally choose payment contracts, trading off differences in enforcement and efficiency between financial markets in different countries. I find that the ability of firms to switch contracts is central to the reaction of trade to variations in financial conditions. Numerical experiments with a two-country version of the model suggest that limiting the choice between payment contracts reduces traded quantities by up to 60 percent.
Keywords: F30; F12; G21; 330; trade finance; payment contracts; trade patterns; financial crisis